A REVIEW AND PROPOSED AMENDMENTS OF VARIOUS RESPONSIBILTIES MENTIONED IN INDIAN GOVERNMENT POLICIES OF E-WASTE MANAGEMENT (International Journal of Engineering Sciences & Management Research, 2016)
People of this 21st century always tempt to change their electronic goods with their newer model within less than 6 months span and this is all thanks to new trendy gadgets coming into the market every month. Its okay, you are purchasing a new one but what about the old ones. Throwing them into the dustbin is not the proper idea of disposing them. It is leading to the growing piles of e-waste which creates problems mainly for the ecology and directly or indirectly for the living beings around there through air, water and soil pollution. Thus it becomes mandatory to control this hazardous situation so that it will not convert into uncontrollable. Thus, for avoiding this kind of scenario, Government of India has laid down various rules, regulations and policies. Through this paper, we will throw light on them and include some amendments for more effectiveness of them.